ANALYSIS OF AN ENHANCED AND RELIABLE BALANCE MAINTENANCE COSTS AND DISTRIBUTED ENERGY IN CLOUD DATA CENTERS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The achievements of cloud computing services have led to large, managed and very expensive computing infrastructures. In particular, the operating costs of major infrastructure are dominated by power supply and various solutions must be introduced to reduce such operating costs and make the entire infrastructure sustainable. Typically, data center operators face three significant problems with the operation of their data centres: increased electricity bills, increasing carbon footprints and unexpected power outages.For this purpose the operation of micro grid data centers is a good choice because microgrid solutions can improve energy efficiency, sustainability and electrical services reliability. We consider EcoMultiCloud as an already proposed charging strategy for multi-objectif charging strategies in the literature and adapt it to the presence of renewable energy sources. The cost savings are therefore achieved during the load assignment process when virtual machines (VMs), by considering the energy costs variations and the presence of renewable energy production, are assigned to a data center of the considered infrastructure.For a specific infrastructure made up of four data centres, performance is analyzed. Results show that, while intermittent and highly variable, in geographical data centers renewable energy can be efficiently exploited by the implementation of an intelligent charge allocation strategy. The results also confirm that EcoMultiCloud is extremely flexible and appropriate for the scenario considered.